2009
DOI: 10.1007/s11101-008-9119-z
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer evaluation of structurally diverse Amaryllidaceae alkaloids and their synthetic derivatives

Abstract: Plants of the Amaryllidaceae family have been under intense scrutiny for the presence of the specific metabolites responsible for the medicinal properties associated with them. The study began in 1877 with the isolation of alkaloid lycorine from Narcissus pseudonarcissus and since then more than 100 alkaloids, exhibiting diverse biological activities, have been isolated from the Amaryllidaceae plants. Based on the present scientific evidence, it is likely that isocarbostyril constituents of the Amaryllidaceae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…Many factors thus seem involved in the anticancer properties of lycorine and a clear mechanism remains to be determined. Nevertheless, the anticancer properties of lycorine have drawn significant attention from chemists [5,6,[11][12][13]. In the present study we report the synthesis of some novel lycorine derivatives and the evaluation of their in vitro anticancer activities.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Many factors thus seem involved in the anticancer properties of lycorine and a clear mechanism remains to be determined. Nevertheless, the anticancer properties of lycorine have drawn significant attention from chemists [5,6,[11][12][13]. In the present study we report the synthesis of some novel lycorine derivatives and the evaluation of their in vitro anticancer activities.…”
Section: Introductionmentioning
confidence: 91%
“…Plant species belonging to the Amaryllidaceae family have been well known for centuries to exhibit diverse medicinal properties. Many of these plants have been used historically for the treatment of cancer, since the oil of the daffodil Narcissus poeticus L. was used by Hippocrates of Kos [5]. The application of narcissus oil in cancer management continued during the middle ages in China, North Africa and Central America [6].…”
Section: Introductionmentioning
confidence: 99%
“…These alkaloids 15 can mostly be classified as belonging to one of eight skeletally distinct subclasses all derived biosynthetically from a common precursor, norbelladine. [1][2][3] Clivonine (1), along with homolycorine (2), hippeastrine (3) and lycorenine (4) are prominent members of the lycorenine subclass; these alkaloids 20 feature a tetracyclic 2-benzopyrano-[3,4-g]indole skeleton and display growth inhibition of various tumour cells, [4][5][6] DNA binding properties, 7 anti-viral activity, 8,9 antifungal activity, 10 and insect antifeedant activity 11 ( Figure 1). 12 (+)-Clivonine (1) was first isolated as white prisms in 25 0.0007% yield from an ethanolic extract of freshly collected rhizomes and leaves of Clivia miniata Regel in 1956 by Wildman, who also tentatively proposed the correct gross topology of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…It isolated 14 Galanthamine alkaloids from Lycoris herb(figure 2), Galanthamine (18) isolated from L.haywardii [15] ; Galanthamine N-oxide(19) isolated from L.incanata [11] ; lycoramine (20) and Lycoramine N-oxide (21)and Sanguinine N-oxide (24) isolated from L.haywardii [4] ; O-demethyllycoramine (22) isolated from L.aurea [16] ; Sangiiinine(23) isolated from L.sanguinea [12] ; epi-galanthamine(25) isolated from L.squamigera [8] ; Narwedine(26), Norgalanthamine (27) and N-allylnorgalanthamine(28) isolated from L.guangxiensis [10] ; N-demethyllycoramine (29) isolated from L.haywardii [15] ; Norsanguinine (30) and norbutsanguininem(31) isolated from L.sanguinea [27] .…”
Section: Galanthamine Type Alkaloidsmentioning
confidence: 99%
“…Galantamine the performance of AchE inhibition is competitive reversible inhibition, the role of the IC50 is 1.9 μmol/L [27] ; 1-O-acetyllycorine of Lycorine type alkaloids has significant inhibitory activity and its intensity is equal to 2 times of Galanthamine, Lycorine of Lycoris type alkaloids, 1,2 diacetyl Lycorine anti-AchE activity is poor [28] ; In addition, the study also found that montanine of AchE showed some inhibition, the strength of galanthamine was slightly lower [29] . Narciprimine and 6-Hydroxycrinamine also has anti-AchE activity [30] .…”
Section: Anti-tumor Effectmentioning
confidence: 99%